Implementasi Asesmen Diagnostik Kurikulum Merdeka Dalam Pembelajaran Bahasa Indonesia di SMP Aisyiyah Boarding School Pinrang: Implementation of the Independent Curriculum Diagnostic Assessment in Indonesian Language Learning at Aisyiyah Boarding School Pinrang Middle School - Amanda, Amanda; Ramly, Ramly; Sultan, Sultan (Journal Studies in Indonesian Language and Literature, 2025)
Diagnostic assessment plays a key role in the Kurikulum Merdeka by helping educators understand the individual needs of students and design effective learning experiences. When implemented properly, it can be a powerful tool in ensuring that every student receives the necessary support to maximize their learning potential. This study aims to describe the forms, implementation, and challenges of conducting diagnostic assessments in Indonesian language learning under the Kurikulum Merdeka at SMP Aisyiyah Boarding School Pinrang. Using a qualitative approach with descriptive methods, the study reveals that cognitive diagnostic assessments in seventh-grade classes are conducted through initial assessments, while non-cognitive diagnostic assessments use questionnaires. The implementation of diagnostic assessments has been carried out well, with teachers following teaching modules, although not yet optimally. Several challenges hinder effective application, including students' fluctuating moods, lack of interest in the subject matter, time constraints, and large class sizes. These factors make the assessment process more complex, both technically and psychologically, affecting the quality of results and the effectiveness of learning.